Dietary Carotenoids and the Risk of Invasive Breast Cancer - Mignone, Laura I. (2009)
Certain classes of vitamins and nutrients found in fruits and vegetables have been of particular interest in relation to cancer prevention, owing to their potential anti-carcinogenic properties. We examined the association between certain fruits, vegetables, carotenoids, and vitamin A and breast cancer risk in a large population based case-control study of women residing in the states of Massachusetts, New Hampshire, and Wisconsin. The study was comprised of 5,707 women with incident invasive breast cancer (2,363 premenopausal women and 3,516 postmenopausal women) and 6,389 population controls (2,594 premenopausal women and 3,516 postmenopausal women). In an interview women were asked about their intake of carotenoid rich fruits and vegetables five years prior to a referent date. An inverse association was observed among premenopausal women was for high levels of vitamin A (OR: 0.82, 95%CI: 0.68–0.98, p for trend = 0.01), β-carotene (OR: 0.81, 95% CI 0.68–0.98, p for trend = 0.009), α-carotene (OR: 0.82, 95% CI: 0.68–0.98, p for trend = 0.07), and lutein/zeaxanthin (OR: 0.83, 95% CI 0.68 – 0.99, p for trend = 0.02). An inverse association was not observed among postmenopausal women. Among premenopausal women who reported ever smoking, these results were stronger than among never smokers, although tests for interaction were not statistically significant. Results from this study are comparable to previous prospective studies and suggest that a high consumption of carotenoids may reduce the risk of pre but not post menopausal breast cancer, particularly among smokers.